Psychological counselling interventions to improve perceived quality of life and counter anxiety and depression in pulmonary-arterial-hypertension patients: A clinical trial - Emilia TARANTINO; Pietro CRESCENZO; Maria CAMPOBASSO; Francesca D’ALESSANDRO; Paola ARGIENTO; Emanuele ROMEO; Stefano GHIO; Patrizio VITULO; Francesco PARISI; Massimiliano MULÈ; Carlo ALBERA; Carmine Dario VIZZA; et al. (Journal of Health and Social Sciences)
Introduction: Pulmonary Arterial Hypertension (PAH) is a rare and progressive disease, frequently associated with a worsening of perceived quality of life as well as anxiety and depression symptomatology. Psychological counselling helps the patient understand the diagnosis and prevent the onset of psychopathologies. This study evaluates the effect of counselling sessions on anxiety and depression as well as the impact on self-reported quality of life in patients with PAH. Methods: Patients with a diagnosis of PAH were recruited at the Monaldi Hospital (Naples). An EQ-5D 3L que- stionnaire was administered to all patients at baseline (pre-session), three months (post-session) after the last session to patients who received psychological counselling (experimental group, EG) and after the first questionnaire to patients who did not (control group, CG). The EQ-5D index and EQ-VAS score were analysed in both groups. Results: A sample of 50 patients with a PAH diagnosis was evaluated; among them 6% had mild PAH, 66% moderate PAH, and 28% severe PAH. The majority (53%) did not receive psychological counselling. All patients showed no significant difference in EQ-5D index (P > 0.05), EQ-VAS score (P > 0.05), and the anxiety/depression dimension (P >.05) at baseline. However, between pre- and post-session evaluations, the analysis showed a significant change in the EQ-VAS score (P = 0.00) and the anxiety/depression dimension (P = 0.02) in the EG. In the CG, there was a similar change in the anxiety/depression dimension (P = 0.00) but not in the EQ-VAS score (P = 0.05) in CG. The z-test revealed significant intergroup relations, showing that the EG had a 37% increase in perceived quality of life and a 9% reduction in anxiety and depression, while a 12% reduction was observed for the CG’s perceived quality of life and a 44% increase in anxiety and depression. Discussion and Conclusions: This study showed that patients with PAH who received psychological support impro- ved their health-related quality of life by reducing anxiety and depression symptomatology. Our findings highlight the impact of psychological support in the treatment of patients with PAH.